"Doing CRISPR": The novel case of Atlantic salmon, science and industry. (29th November 2018) - Dankel, Dorothy Jane
Abstract : Salmon farming is a key industry in Norway, with firsthand value of more than 60 billion Norwegian crowns in 2017. The salmon industry is a driving force for biotechnological applications in the marine sector. The recent release of the Atlantic salmon reference genome offers new opportunities to solve major aquaculture bottlenecks that currently limit expansion of the industry. One major bottleneck is the genetic impact of escaped farmed salmon on wild populations. To solve this problem, the industry can use sterile salmon in production. As shown by Wargelius et al., sterile salmon can be made by preventing the formation of germ cells through genome editing using the CRISPR-Cas9 method. This approach solves problems of genetic introgression and precocious maturation. However, genome editing of animals, especially for human consumption, raises ethical as well as safety and legal questions. These social and ethical aspects can have tremendous impact in analyzing the final result of salmon farming (e.g., consumer acceptability of a fresh or frozen filet or similar salmon product) but also can be examined "upstream" by describing and assessing the research communities that promote and carry out the science that underpins the salmon industry. Who produces the scientific "facts" that govern the Norwegian aquaculture industry? How do these scientific communities work together? What are the societal impacts of this science? This article uses ethnographical observation and interviews to describe the state-of-the-art of CRISPR gene-editing procedures currently employed in the science and industry collaboration in Norway.